YIELD, PHYSICAL AND CHEMICAL-TECHNOLOGICAL PROPERTIES OF GRAIN AND FLOUR OF NEW WINTER WHEAT VARIETIES IN DIFFERENT AGROECOLOGICAL CONDITIONS - Dolijanović, Željko K. (Journal of Agricultural Sciences (Belgrade), 2025)
The need for global food security requires an increase in wheat production, as the third most common crop in the world with a significant role in the global and Serbian economy. Although breeding and agrotechnical measures contribute to yield growth, agriculture faces challenges such as climate change, land degradation and rising input costs, which require new approaches to production stability. The aim of the research was to identify differences in grain yield and quality between the widely used wheat variety Pobeda and the new wheat variety ML Grigorija, taking into account the influence of genotype and external conditions. The yield and physicochemical properties of grain and flour of ML Grigorija and Pobeda were examined at six locations in Serbia during 2021/22. and 2022/23. The experiments were organized according to a randomized design with three replications, with standard agrotechnical measures. The yield was calculated and corrected to standard moisture, while the physicochemical and rheological properties were analyzed in accredited laboratories according to SRPS ISO standards. Technological parameters of wheat were also examined. The obtained results were processed statistically using the analysis of variance method, and for individual comparisons the least significant difference test (lsd test) was used. The results showed significant differences in yield, physical and technological properties depending on the factors examined. The ML Grigorija variety achieved high yields and good technological quality in favorable conditions, while Pobeda had more stable physical properties and better test stability, which indicates that the selection of the genotype adapted to environmental conditions enables the achievement of high and stable yields and quality.
Keywords: wheat (Triticum aestivum L.), quality, grain yield, variety, agroecological conditions.